Exposure to X-Ray and Fecundity at the Radiographer - M. Al-khudhory, Dr. Mudhafar Abdulhussein (American Journal of Biology and Natural Sciences, 2026)
Fecundity, is refers to ability of achieving pregnancy and the probability to achieve a live birth, including all steps that leads to form embryo, beginning from fuse of the gametes (sperm fertilize the oocyte) forming zygote and all early stages of embryo ending to fetus. the fertility may be effected by factors which leads to declines. Medical devices such as x-ray devices can be considered from these factors. Exposure to high doses of x-ray may be effect on fertility, but low doses may be not. This study aimed to clarify the impact of the x-ray on fecundity. A population sample (radiographer) was recruited in this work, they are different in personal characteristics but they are similar in working conditions and they were exposed to almost the same doses of x-ray.